Certainty of Terms and Leases: Curiouser and Curiouser - LOW, Kelvin Fatt Kin (Institutional Knowledge at Singapore Management University, 2012)
The common law rule that requires leases to have a fixed terminus from the outset is one that has been much criticised. In Berrisford v Mexfield Housing Co-operative Ltd, the Supreme Court managed to blunt its effect by suggesting that most leases of uncertain duration can be transformed into 90-year tenancies. However, it is suggested that their Lordships have possibly misunderstood and overstretched an ancient common law ‘rule’ and have not fully considered some of the implications of their decision.